2015
DOI: 10.1007/s10973-014-4355-5
|View full text |Cite
|
Sign up to set email alerts
|

Vogel–Fulcher analysis of relaxor dielectrics with the tetragonal tungsten bronze structure: Ba6MNb9O30 (M = Ga, Sc, In)

Abstract: In-depth analysis of the relaxor behaviour of Ba 6 MNb 9 O 30 (M= Ga, Sc, In) tetragonal tungsten bronze (TTB) ceramics was carried out. Powder x-ray diffraction and scanning electron microscopy were performed in order to confirm the formation of desired phases and to determine the microstructure. Low-temperature dielectric spectroscopy was used in order to characterise the dielectric properties of these materials; the degree of relaxor behaviour were investigated in relation with the increase of ionic radius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…In previous research, temperature-dependent powder neutron diffraction (TDPND) and microstructural characterisation by scanning electron microscopy (SEM) confirmed the nature of the phases formed and contributed to their crystallographic identification [41]. Moreover, the origin of the polar response and the nature of the relaxor behaviour were established by combining the results of the structural investigations with the dielectric properties inspected by immittance spectroscopy (IS) [7,41], whilst the dynamics of dielectric relaxation of dipoles was understood by fitting the dielectric data (permittivity and loss) with the VogelFulcher (VF) and the universal dielectric response (UDR) models [42].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous research, temperature-dependent powder neutron diffraction (TDPND) and microstructural characterisation by scanning electron microscopy (SEM) confirmed the nature of the phases formed and contributed to their crystallographic identification [41]. Moreover, the origin of the polar response and the nature of the relaxor behaviour were established by combining the results of the structural investigations with the dielectric properties inspected by immittance spectroscopy (IS) [7,41], whilst the dynamics of dielectric relaxation of dipoles was understood by fitting the dielectric data (permittivity and loss) with the VogelFulcher (VF) and the universal dielectric response (UDR) models [42].…”
Section: Introductionmentioning
confidence: 85%
“…For obtaining Ba 6 GaNb 9 O 30 pellets, the powders were pressed in a 10-mm-diameter uniaxial stainless steel die to 1 tonne, producing a pressure of around 200 MPa followed by sintering in a tube furnace for 12 h at 1250°C (heating and cooling rates were of 10 K min -1 ). Phase formation was confirmed by powder X-ray diffraction and temperature-dependent powder neutron diffraction; at room temperature, diffraction data were refined with the centrosymmetric tetragonal space group P4/mbm [5,41,42].…”
Section: Methodsmentioning
confidence: 99%
“…The frequency dependence of the temperature of maximum permittivity, T m , in relaxors can be described by the VogelFulcher law (4) which provides some insights into the dynamics of dielectric relaxation [39][40][41].…”
Section: Dielectric and Relaxor Ferroelectric Propertiesmentioning
confidence: 99%
“…We have shown that Vogel-Fulcher fits are very sensitive. Constraining some of the fundamental relaxation parameters to physically sensible values or varying the fitting range itself, results in a large range of values associated with the dielectric relaxation processes; restriction of the frequency domain due to experimental noise or instrumentation limits also has a dramatic influence on the values obtained [40].…”
Section: Introductionmentioning
confidence: 99%